Curcuma treatment prevents cognitive deficit and alteration of neuronal morphology in the limbic system of aging rats. Issue 3 (12th January 2017) - Vidal, Blanca; Vázquez‐Roque, Rubén A.; Gnecco, Dino; Enríquez, Raúl G.; Floran, Benjamin; Díaz, Alfonso; Flores, Gonzalo
Abstract: Curcuma is a natural compound that has shown neuroprotective properties, and has been reported to prevent aging and improve memory. While the mechanism(s) underlying these effects are unclear, they may be related to increases in neural plasticity. Morphological changes have been reported in neuronal dendrites in the limbic system in animals and elderly humans with cognitive impairment. In this regard, there is a need to use alternative therapies that delay the onset of morphologies and behavioral characteristics of aging. Therefore, the objective of this study was to evaluate the effect of curcuma on cognitive processes and dendritic morphology of neurons in the prefrontal cortex (PFC), the CA1 and CA3 regions of the dorsal hippocampus, the dentate gyrus, and the basolateral amygdala (BLA) of aged rats. 18‐month‐old rats were administered curcuma (100 mg/kg) daily for 60 days. After treatment, recognition memory was assessed using the novel object recognition test. Curcuma‐treated rats showed a significant increase in the exploration quotient. Dendritic morphology was assessed by Golgi–Cox staining and followed by Sholl analysis. Curcuma‐treated rats showed a significant increase in dendritic spine density and dendritic length in pyramidal neurons of the PFC, the CA1 and CA3, and the BLA. The preservation of dendritic morphology was positively correlated with cognitive improvements. Our results suggest that curcuma induces modification of dendritic morphology in the aforementioned regions. These changes may explain how curcuma slows the aging process that has already begun in these animals, preventing deterioration in neuronal morphology of the limbic system and recognition memory. Abstract : We examined the effect of curcuma on aging rats. Neural dendritic morphology in the prefrontal cortex, the hippocampus and the basolateral amygdala was measured after 8 weeks of curcuma administration in the aging animals. Curcuma ameliorated the effect of aging on memory process and dendritic morphology in aging rats.